Ab-Initio Calculation of the Electrical Conductivity, Optical Absorption, and Reflectivity of the 2D Materials SnC and NbC - Nadxiieli Delgado; Osiris Salas; Erick Garcés; Luis Fernando Magaña (Crystals, 2023)
Using density functional theory (DFT), we performed first-principles calculations of the electrical conductivity, optical absorption, and reflectivity for the 2D carbides SnC and NbC. We calculated the electronic energy band structure of the materials. We performed the calculations without considering the spin–orbit coupling (SOC) term and including it. We determined that 2D SnC is a semiconductor material and 2D NbC is a conductor. We compared the optical absorption and reflectivity with those of graphene. We found that the 2D SnC and graphene optical absorptions in the infrared region are similar and small; the corresponding values for 2D NbC are approximately ten times larger. In the visible range, the absorption values for 2D SnC and 2D NbC are of the same magnitude and much more significant than graphene. We found that the 2D NbC optical absorption for the ultraviolet region was close to zero. Graphene and 2D SnC have similar maximum values for absorption but at different energies. We determined that graphene reflectivity is larger but similar to that of 2D NbC, and that the 2D SnC reflectivity is near zero. Finally, the 2D NbC electrical conductivity value was about ten times larger than the corresponding value for 2D SnC. As expected, when there was a change of dimensionality, the related 3D materials showed a vastly different value for the electrical conductivity. The 2D materials showed conductivities significantly smaller than those of 3D materials in both cases. The results we obtained for 2D SnC and 2D NbC when we included the SOC term showed that the electrical conductivity for 2D SnC increased by 13.18% and 2D NbC by 18.16%. The optical properties changed, particularly the location of the peaks in the optical absorption and reflectivity.